2014
DOI: 10.1001/jama.2014.11479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhanced Information, Values Clarification, and Removal of Financial Barriers on Use of Prenatal Genetic Testing

Abstract: Importance Prenatal genetic testing guidelines recommend providing patients with detailed information to allow informed, preference-based screening and diagnostic testing decisions. The effect of implementing these guidelines is not well understood. Objective Toanalyze the effect of a decision support guide and elimination of financial barriers to testing on use of prenatal genetic testing and decision-making among women of varying literacy and numeracy levels. Design Randomized trial conducted from 2010-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 23 publications
1
127
0
Order By: Relevance
“…The parent study for the current analysis found that women who were randomized to use an interactive decision-support guide made more informed testing choices than women randomized to usual care 12 . That a disparity by site of care in recall of diagnostic testing discussions was only seen in the usual care group in the current study may suggest that this kind of decision support could prove a useful adjunct to the current paradigm of counseling women and assure provision of consistent information to all women.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The parent study for the current analysis found that women who were randomized to use an interactive decision-support guide made more informed testing choices than women randomized to usual care 12 . That a disparity by site of care in recall of diagnostic testing discussions was only seen in the usual care group in the current study may suggest that this kind of decision support could prove a useful adjunct to the current paradigm of counseling women and assure provision of consistent information to all women.…”
Section: Discussionmentioning
confidence: 88%
“…We conducted a secondary analysis of a randomized controlled trial that explored the effect of providing a prenatal testing decision-support guide that included enhanced information about prenatal testing and its voluntary nature, along with a series of values clarification exercises, and removing financial barriers on use of prenatal screening and diagnostic tests 12 . A diverse group of 710 English and Spanish speaking women of varying literacy levels and sociodemographic backgrounds was recruited for study participation at less than 20 weeks gestation.…”
Section: Methodsmentioning
confidence: 99%
“…To safeguard informed decision‐making, emphasis has to be placed on further development of information tools and maintaining good counseling. The use of decision aids29, 30 or visuals aids such as an informational film31 may have a positive effect on informed decision‐making by improving knowledge and assisting women in making decisions that are consistent with their values. Special attention should be given to women with a lower educational level and/or inadequate health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some women may prefer diagnostic testing or no testing, regardless of age. 31 It is appropriate therefore to offer diagnostic testing, screening, or the option of no testing to women of all ages. 32,33 The offer of prenatal screening requires discussion of the pros and cons of all test options, including the detection rates, screen positive rates, and recommended follow up if an abnormal result is obtained (Table 2).…”
Section: Smfm Consult Seriesmentioning
confidence: 99%